CORRELATION OF STRESS HYPERGLYCEMIA WITH BARTHEL INDEX IN ACUTE NON-HEMORRHAGIC STROKE PATIENTS AT NEUROLOGY WARD OF RSUD ARIFIN ACHMAD PEKANBARU - Jaro Shafi’i; Riki Sukiandra; Mukhyarjon " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTThe raising of blood glucose that occurs due to disruption of the regulation of blood glucose which is part of the non-specific reaction to the occurrence of stress or tissues damage called stress hyperglycemia. Stress hyperglycemia is common in acute diseases such as stroke, which significantly affect patient outcomes that can be assessed with the Barthel Index. The aim of this study was to find out the relationship between stress hyperglycemia with Barthel index in patients with acute non-hemorrhagic stroke. This study using analytic observational method with cross sectional design. The sample are acute non-hemorrhagic stroke patients totaling 38 patients who conform the inclusion criterias. Results of the study of 38 patients, is the prevalence of stress hyperglycemia prevalence cases totaled 23 people (60.52%) in non-acute hemorrhagic stroke. Showed that Barthel Index acute non-hemorrhagic stroke patients are heavy dependence (21-61) of 21 patients (55.26%), followed by 3 patients (7, 89%) with a full dependence (0-20), 13 patients ( 34.21%) with moderate dependence (62-90) and 1 patient (2.63%) with mild dependence (91-99). There is no correlation between stress hyperglycemia with Brthel Index with the value of (r = 0.059) and the value of (p = 0.654). So, based on this research most of the respondents in this study suffered from stress hyperglycemia but there is no correlation between stress hyperglycemia with Barthel Index and most of the patients has a bad interpretation of Barthel Index. Keywords: Stress hyperglycemia, Barthel Index, non-hemorrhagic stroke acute,ADL